Bioengineered strategies for tendon regeneration - Gonçalves, Ana Isabel Silva (2016)
Their important mechanical function predisposes tendons to injury and rupture, becoming a worldwide clinical problem. Commonly injured tendons include the rotator cuff, finger flexors, patellar, and Achilles tendon [1]. As poor cellular and vascular tissues [2], tendons present some healing constraints, typically requiring surgical intervention. Available reparative surgeries rely on tissue replacement with auto- or allografts [3], which are often accompanied with donor site morbidity, pain, inferior functionalities, and eventually graft failure. Due to the market demand, commercial substitutes for tendon repair have been developed as biological and synthetic scaffolds.